The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1002/elan.201300526
|View full text |Cite
|
Sign up to set email alerts
|

Nanohybrid Materials Consisting of Poly[(3‐aminobenzoic acid)‐co‐(3‐aminobenzenesulfonic acid)‐co‐aniline] and Multiwalled Carbon Nanotubes for Immobilization of Redox Active Cytochrome c

Abstract: The development of a new surface architecture for the efficient direct electron transfer of positively charged redox proteins is presented. For this reason different kinds of polyaniline terpolymers consisting of aminobenzoic acid (AB), aminobenzenesulfonic acid (ABS) and aniline (A) with different monomer ratios were synthesized. The P(AB‐ABS‐A) were grafted to the surface of multiwalled carbon nanotubes (MWCNTs). FTIR measurements prove the covalent binding to the carboxylic groups of the MWCNTs while conduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 45 publications
0
9
0
Order By: Relevance
“…So far, in order to provide a better environment for cyt c to function, different electrodes which are mainly based on nanomaterials (e.g. carbon nanotubes, graphene and nanoparticles) have been used [40][41][42][43][44][45] . Nevertheless, these attempts might not be sufficient to preserve the whole cyt c activity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…So far, in order to provide a better environment for cyt c to function, different electrodes which are mainly based on nanomaterials (e.g. carbon nanotubes, graphene and nanoparticles) have been used [40][41][42][43][44][45] . Nevertheless, these attempts might not be sufficient to preserve the whole cyt c activity.…”
Section: Introductionmentioning
confidence: 99%
“…For example, it is well known that functional properties of cytochrome c (cyt c ) were hampered because it adsorbed strongly on electrodes ( e.g., Pt, Hg, Au, and Ag) because this adsorption caused large conformational changes and denaturation. Moreover, direct electron transfer between cyt c and unmodified electrode surface is slow due to undesired contact between the prosthetic group and the electrode . So far, in order to provide a better environment for cyt c to function, different electrodes which are mainly based on nanomaterials ( e.g., carbon nanotubes, graphene, and nanoparticles) have been used. Nevertheless, these attempts might not be sufficient to preserve the whole cyt c activity. By forming planar membranes on solid support as a mean of electrode surface modification, (i) a natural biocompatible means of cyt c –substrate interactions and (ii) effective, highly dynamic platform to host biomolecules can be achieved. , Such a system improves the protein–membrane–substrate communication for the development of highly sensitive and efficient biosensors.…”
Section: Introductionmentioning
confidence: 99%
“…Such nanohybrids consisting of CNTs and polyaniline‐derivates have been synthesized 13,14 and used in a lactose biosensor 15. Immobilization of cytochrome c (cyt.c) on the negatively charged surface of a nanohybrid (MWCNT‐P(AB‐ABS‐A)) resulted in an increase in electroactive surface concentration of cyt.c in comparison to unmodified MWCNTs 16.…”
Section: Electrochemical Parameters Of Au‐aht/[mwcnt‐p(abs‐a)/hthp] Amentioning
confidence: 99%
“…For the negatively charged nanohybrid the surface concentration at saturation was calculated to be either 3.1 pmol cm −2 ( n =6). For comparison, the surface concentration of cytochrome c (taking the size of 10.2 nm 2 ), immobilized on nanostructured surface, was reported to be 16.2 pmol cm −2 16.…”
Section: Electrochemical Parameters Of Au‐aht/[mwcnt‐p(abs‐a)/hthp] Amentioning
confidence: 99%
“…By increasing the degree of sulfonation, the peak current of the redox protein could also be enhanced. The study showed that the immobilization of cyt c was possible and that a more efficient DET to the nanostructured electrode could be achieved [ 38 ].…”
Section: Introductionmentioning
confidence: 99%